Analisa faktor-faktor penyebab perubahan efisiensi boiler jenis pulverized coal fired forced circulation sub-critical pressure menggunakan metode tak langsung - Muhammad Sagaf (Faculty of Industrial Technology Universitas Islam Indonesia, 2018)
The Boiler is one of the equipment in the steam power plant which their reliability will be decreased by annually. Boiler degradation can be observed by the decreasing value of boiler efficiency every year. To maintain the efficiency it is necessary to know the main cause of degradation factors. PLTU Tanjung Jati B Unit 3 and 4 using pulverized coal fired boilers with forced circulation and sub-critical pressure type, the steam capacity is 2x2280 tons / hour to generate electrical energy of 2x660 MW.Boiler Efficiency is calculated by indirect method with uncertainty rate (0.4% -0.8%) in every boiler heat loss. The highest efficiency of boiler Unit 3 was achieved during Commercial Operation Date (COD) in 2011 with 89.71%, while Unit 4 achieved on the 2nd test performance in 2013 with 89.61%. The lowest boiler efficiency value for Unit 3 on the 9th performance test in 2016 with 88,36%, and Unit 4 was on 9th performance test in 2016 with to 87,48%. The degradation of Unit 3 boiler efficiency during 6 years is 1.35% or 0.225% per year. While the degradation of Unit 4 boiler efficiency during 6 years is 2.13% or 0.355% per year. The major of boiler heat loss were from exhaust gas (L1), moisture content of burning hydrogen in fuel (L3) and heat loss due to the moisture in the fuel (L2). The main factors losses in boiler is caused by ash deposits in the economizer area, it make inhibition of heat transfer from (flue gas) to economizer tube, the others from the use of three types of coal which have different characteristics.